Designing electrolyte with multi-ether solvation structure enabling low-temperature sodium ion capacitor - Dongming Liu; Mengfan Pei; Xin Jin; Lin Wang; Wanyuan Jiang; Borui Li; Runyue Mao; Xigao Jian; Fangyuan Hu (International Journal of Extreme Manufacturing)
Sodium-ion hybrid capacitors (SICs), which combine the high energy density of batteries with the high power density and long cycle life of capacitors, are considered promising next-generation energy storage devices. Ensuring the performance of SICs in low-temperature environments is crucial for applications in high-altitude cold regions, where the desolvation process of Na ^+ and the transport process in the solid electrolyte interphase (SEI) are determinant. In this paper, we proposed a multi-ether modulation strategy to construct a solvation sheath with multi-ether participation by modulating the coordination of Na ^+ and solvents. This unique solvation sheath not only reduces the desolvation energy barrier of Na ^+ , but more importantly forms a Na _2 O-rich inorganic SEI and enhances the ionic dynamics of Na ^+ . Benefiting from the excellent solvation structure design, SICs prepared with this electrolyte can achieve energy density of up to 178 Wh·kg ^‒1 and ultra-high power density of 42 390 W·kg ^‒1 at room temperature. Notably, this SIC delivers record-high energy densities of 149 Wh·kg ^‒1 and 119 Wh·kg ^‒1 as well as power densities of up to 25 200 W·kg ^‒1 and 24 591 W·kg ^‒1 at ‒20 °C and ‒40 °C, respectively. This work provides new ideas for the development of high-performance SICs for low-temperature operating environments.